1975
DOI: 10.1159/000264731
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Cataract and Mitosis

Abstract: X-irradiation of frog eyes with natural and experimentally induced differences in lenticular mitotic activity reveals cataractogenesis to be dependent on the proliferative activity of the germinative zone of the lens epithelium. It has also been found that G₀ cells are sufficiently vulnerable to X-rays to cause opacity if cell division is allowed to occur following irradiation. In every case of X-ray-induced lens opacification, a disruption of the radiating columns shows a strong correlation to the severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Radiation-induced cataracts have been studied in cancer patients (16), patients under- (20,21). Cataract severity and time of onset are directly related to the number of genomically damaged cells attempting differentiation (fibergenesis) (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-induced cataracts have been studied in cancer patients (16), patients under- (20,21). Cataract severity and time of onset are directly related to the number of genomically damaged cells attempting differentiation (fibergenesis) (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…W o r g u l and R othstkin [44] also found that depressing the mitotic activity of frogs by keeping them at very low temperatures reduced the in cidence and severity of cataracts produced by ionizing radiation. They con cluded that mitosis 'transduced' epithelial cell damage into cataractous changes and that inhibition of mitosis prevented this transduction.…”
Section: Dna Repair In the Lensmentioning
confidence: 95%
“…While other environmental insults might also result in formation of posterior subcapsular cataracts, radiation-induced cataracts are generally associated with this form of lens opacification (32,33). Its development is directly related to radiation dose and also depends on the rate at which damaged lens epithelial cells divide, aberrantly differentiate and migrate to the posterior pole (34). Although the precise inducing mechanism is not known, it is generally accepted that genomic damage results in altered cell division, transcription and/or abnormal lens fiber cell differentiation that leads to cataract development (35,36).…”
Section: Introductionmentioning
confidence: 99%